'A psychological riddle demanding a solution'. Crowd psychology and the Finnish Civil War of 1918. Issue 5 (4th July 2022) - Pietikainen, Petteri
ABSTRACT: Right after the Finnish Civil War of 1918, the first treatises discussing the insurgents (the Reds) in crowd psychological terms were published. Between 1918 and the early 1920s, several Finnish authors used Gustave Le Bon's and other crowd psychologists' ideas of suggestion, mental epidemics, and the dangers of socialism in their interpretations of the aborted revolution. The article argues that the use of crowd psychology in the years following the Finnish Civil War was an attempt to articulate in objective, scientific language an emotional and moral reaction to the shock of seeing a nation violently divided and tearing itself apart. Intrinsic to Finnish interpretations of crowd psychology were the increasing antagonism between socialists and anti-socialists, the influence of Bolshevism on the worker's movement, the importance attributed to the 'racial' qualities of the people, and the impact of the Civil War on the educated classes – all issues that are easy to relate to wider European and global contexts. This article lends support to the thesis that crowd psychology was an influential intellectual construction that had great heuristic value among contemporaries from the late nineteenth century to World War II.